PENGARUH PEMBERIAN RANSUM DENGAN DOSIS HERBAL YANG BERBEDA TERHADAP KUALITAS EKSTERNAL TELUR AYAM PERSILANGAN - Muntasiah, Dewi; Tantalo, Syahrio; Nova, Khaira; Sutrisna, Rudy (Jurnal Riset dan Inovasi Peternakan, 2019)
This study aims to determined the effect of giving rations with different of  herbs dosages on external quality of crossbred chicken eggs and to find out the best dosage of herbs in ration that affect the external quality of crossbred chicken eggs.  This research was conducted in September 2018 in the poultry house of the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung.  The chickens used were   crossbred chickens between male Lohmann brown and female kampong (3/4 Lohmann brown +1/4 kampong) layer phase aged (48 weeks) as many as 20 chickens.  The experimental design used completely randomized design (CRD) with 4 treatments and 5 replications.  The treatment given are a diet with different dosages of herbs, which are, H0: without herbs, H1: 1g / 1kg, H2: 2g / 1kg, H3: 3g / 1kg.  The data obtained were analyzed by analyze of variance using significant level of 5% and followed by least significant different test.  The variables observed were consumption of calcium and phosphorus, egg weight, and shell thickness.  The results showed that different rations with herbs level had a significant effected (P <0,05) on egg weight and did not significant effected (P> 0,05) on calcium intake, phosphorus intake, and shell thickness. Keywords: Rations, Herbs, External quality of eggs, Crossbred chicken